An osmolarity dependent mechanism partially ameliorates retinal cysts and rescues cone function in a mouse model of X-linked retinoschisis - Gehrke, Ella J.; Thompson, Jacob; Kalmanek, Emily; Stanley, Sarah T.; Laird, Joseph; Bhattarai, Sajag; Lobeck, Brianna; Mayer, Sara; Mahoney, Angela; Hassan, Salma; Hsu, Ying; Drack, Arlene (Frontiers in Medicine, 2024)
Introduction X-linked retinoschisis (XLRS) is a vitreoretinal dystrophy caused by RS1 gene mutations which disrupt retinoschisin-1 (RS1) function. Vital for retinal architecture, the absence of functional RS1 leads to the development of intraretinal cysts. Intravitreal injection of a gene therapy for treating XLRS caused ocular inflammation in high dose groups in a phase I/II clinical trial. This study investigates a low dose subretinal gene therapy in Rs1 knockout (Rs1-KO) mice compared to injection of buffer alone. Observation of an unexpected therapeutic effect following the subretinal injection of the hypertonic buffer led to novel findings in XLRS.Rs1-KO mice were subretinally injected with an AAV2/4 vector (n=10) containing the RS1 gene driven by an Ef1α promoter, a hypertonic buffer (n=15) (180 mM NaCl 0.001% F68/PBS (pH 7.4)), or isotonic buffer (n=7) (155.2 mM NaCl 0.001% F68/PBS, pH 7.0). A sham puncture group was also included (n=6). Endpoints included electroretinogram (ERG), optical coherence tomography (OCT), a visually guided swim assay (VGSA), and immunohistochemistry.Unexpectedly, hypertonic buffer-injected eyes had reduced cyst severity at 1-month postinjection (MPI) (p<0.0001), higher amplitudes in cone-dominant ERGs persisting to 5 MPI (5 Hz flicker; p<0.0001; 3.0 Flash; p=0.0033) and a trend for improved navigational vision in the light compared to untreated Rs1-KO eyes. To investigate the role of tonicity on this effect, an isotonic buffer-injected cohort was created (155.2 mM NaCl 0.001% F68/PBS, pH 7.0) (n=7). Surprisingly, hypertonic buffer-injected eyes exhibited a greater reduction in cyst severity and demonstrated improved cone-dominant ERG metrics over isotonic buffer-injected and sham puncture eyes. An immunohistochemistry assay demonstrated greater cone density in hypertonic buffer-injected eyes than untreated Rs1-KO eyes at 5-6 MPI (p=0.0198), suggesting a possible cone preservation mechanism. Moreover, our findings reveal a negative correlation between the peak severity of cysts and long-term ERG amplitudes in cone-dominant pathways, implying that effectively managing cysts could yield enduring benefits for cone function.This study presents evidence that cyst resolution can be triggered through an osmolaritydependent pathway, and early cyst resolution has long-term effects on cone signaling and survival, offering potential insights for the development of novel treatments for XLRS patients.